Toolkit for Cost-Benefit Analysis of Climate Information Services: An outline - Timu, Anne; Aju, Stellamaris; Kramer, Berber (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
To better understand the individual and societal benefits of CIS, IFPRI is developing a toolkit that evaluates the costs and benefits of country-specific CIS packages. The toolkit will go beyond the conventional approach that measures the net present value of gains in farm productivity and profitability to evaluate impacts on a range of other outcome variables that are not traded in the market (for example, more stable and predictable income flows, improved women’s agency, reductions in workload and intra-household labor allocations, and changes in health and behavioral outcomes).